European Governance and Democratic Legitimacy of EU Legislation Formation - Müge Algan (Journal of Business Administration and Social Studies)
The basic of governance approach that is used after the 1990s as a new public administration model is public participation in public policies and government. Organization for Economic Co-operation and Development and the United Nations defined the term governance, which was first introduced by World Bank, with their own approaches and identified different principles. The European Union has created the European Governance model in order to overcome the administrative problems experienced within the Union and to establish a more effective administration approach within the European Union. The main criticism of the governance model is the equal participation right. This article analyses the governance approach of the European Union and the way the European Union provides participation during its legislation processes by examining the European Governance White Paper and Communication, which forms the basis of European Governance, and three other different legislation. This article examines the democratic legitimation of European Governance in the light of numerical data.